MEWUJUDKAN TATA KELOLA PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE): MELALUI OPTIMALISASI PENILAINAN KINERJA, MANAGEMENT TALENTA DAN MANAJEMEN KINERJA PEGAWAI NEGERI SIPIL - Nana Darna; Muhammad Aziz Basari; Mujaddid Faruq (JURISMA : Jurnal Riset Bisnis & Manajemen, 2014)
Good Government Governance means the government is administered effectively and efficiently by developing performance management. So far the performance management program for Civil Servants is still centralized, so that the potential of local knowledge and culture have not been able to be developed. Performance Appraisal and Talent Management is an integrated part of the Performance Management. The implementation of the Civil Service performance appraisal in the previous years still used DP3 (Daftar Penilaian Pelaksanaan Pekerjaan) which still raises doubts in describing accurately the performance of the Civil Service. DP3 was also said to be less flexible to express special characters that distinguish a profession to other professions, and it was said to be risk of subjectivity. The result of DP3 assessment was never discussed or evaluated collectively to obtain feedback from employees. DP3 has not been able to meet the criteria of assessment for employee performance which compares the results of the accomplishment of tasks with the predetermined standard.The implementation of the performance appraisal of civil servants so far has used DP3 as specified in the Government Regulation No.10 of 1979 It is a list that contains the results of assessment of the accomplishment of Performance of Civil Servants within a period of one year made by authorized Assessors. The assessment covers confidential elements, such as  a) loyalty, b) performance, c) responsibility, d) conformity, e) honesty, f) cooperation, g) initiative, and h) leadership. Leadership is only assessed for Civil Servants who have rank above II/a who have certain position.The implementation of talent  management was performed by national or local staffing agencies which were  directed to ensure the effective and efficient administration of  government and development tasks..The implementation of performance management was aimed at generating Civil Service who are professional, responsible, honest, and righteous through the coaching system implemented based on job performance and career system that focused on performance system. Implementation of performance appraisal, talent management and performance management have not been able to realize the Good Governance. It is reflected from the role of civil servants in providing public service that put themselves as bureaucrat, not as public service  provider.In this study we used Qualitative methods. This research was performed by collecting data through observation and interview to the respondents. Respondents are employees comprising one  Head of Badan Kepegawaian dan Diklat Daerah / BKDD Ciamis, one Secretary of BKDD Ciamis, four Heads in charge of staffing BKDD Ciamis by the hope that everyone understand clearly about the reality and the conditions of governance, especially the management of the civil servant performance management.